The Effect of Buddy Reading Strategy on Developing Third Basic Grade Students' Oral Reading Fluency - Al-Khawaldeh, Mohammad; Obaidat, Rania (Jordan Journal of Educational Sciences, 2019)
This study aimed at investigating the effect of buddy reading strategy on developing oral reading fluency among third basic grade students, and whether it would differ according to gender and to the interaction between gender and teaching strategy. To achieve the aims of the study, the researchers adopted and adapted "Florida Oral Reading Fluency Test (FORF, 2009). The subjects of the study consisted of (48) third basic grade students selected from (10) public schools, affiliated to Bani Khinanah Directorate of education. The subjects were also divided into two groups: (24) students in the control group taught by the conventional method, and (24) students in the experimental group taught by buddy reading strategy. The results of the study revealed statistical significant differences in oral reading fluency, due to the teaching method, in the favor of the experimental group subjects taught by buddy reading strategy. The results also revealed statistical significant differences in oral reading fluency, due to gender, in the favor of females, but no statistical significant differences due to the interaction between teaching strategy and gender